Monoamine oxidase: isoforms and inhibitors in Parkinson's disease and depressive illness - Youdim, Moussa B H (Nature Publishing Group, 2006)
A few years after the foundation of the British Pharmacological Society, monoamine oxidase (MAO) was recognized as an enzyme of crucial interest to pharmacologists because it catalyzed the major inactivation pathway for the catecholamine neurotransmitters, noradrenaline, adrenaline and dopamine (and, later, 5-hydroxytryptamine, as well). Within the next decade, the therapeutic value of inhibitors of MAO in the treatment of depressive illness was established. Although this first clinical use exposed serious side effects, pharmacological interest in, and investigation of, MAO continued, resulting in the characterization of two isoforms, MAO-A and -B, and isoform-selective inhibitors. Selective inhibitors of MAO-B have found a therapeutic role in the treatment of Parkinson's disease and further developments have provided reversible inhibitors of MAO-A, which offer antidepressant activity without the serious side effects of the earlier inhibitors. Clinical observation and subsequent pharmacological analysis have also generated the concept of neuroprotection, reflecting the possibility of slowing, halting and maybe reversing, neurodegeneration in Parkinson's or Alzheimer's diseases. Increased levels of oxidative stress in the brain may be critical for the initiation and progress of neurodegeneration and selective inhibition of brain MAO could contribute importantly to lowering such stress. There are complex interactions between free iron levels in brain and MAO, which may have practical outcomes for depressive disorders. These aspects of MAO and its inhibition and some indication of how this important area of pharmacology and therapeutics might develop in the future are summarized in this review.